2019
DOI: 10.3892/ijo.2019.4682
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 7 inhibits plakoglobin expression to promote lung cancer cell growth and metastasis

Abstract: Plakoglobin is a tumor suppressor gene in lung cancer; however, the mechanism by which it is downregulated in lung cancer is largely unknown. The aim of the present study was to investigate whether histone deacetylases (HDACs) regulate plakoglobin expression in lung cancer. The effects of overexpression or knockdown of HDAC7 on plakoglobin were determined using stably transfected lung cancer cell lines. Chromatin immunoprecipitation assays were performed to elucidate the mechanisms underlying the HDAC7-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 47 publications
(55 reference statements)
1
22
0
Order By: Relevance
“…HDAC7 is dysregulated in the many cancers [13][14][15][16][17][18][19] , is correlated with metastasis and poor prognosis, and is the main target of several HDACis [21][22][23] . Although several HDACis have exhibited anti-NPC effects [7][8][9][10][11] , the role and underlying mechanism of HDAC7 in NPC have not been explored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HDAC7 is dysregulated in the many cancers [13][14][15][16][17][18][19] , is correlated with metastasis and poor prognosis, and is the main target of several HDACis [21][22][23] . Although several HDACis have exhibited anti-NPC effects [7][8][9][10][11] , the role and underlying mechanism of HDAC7 in NPC have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that oncogenic roles of HDAC7 are dependent on upregulation of Stat3 and c-Myc 13,14,[39][40][41] . However, we did not observe the effects of HDAC7 knockdown on the expression of c-Myc and Stat3 in NPC cells (data not shown), suggesting that other factors mediate the function of HDAC7 in NPC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have showed that HDAC7 was involved in the malignant phenotype of glioma regulated by ZNF326 [25]. Sang Y et al displayed that HDAC7 facilitated cell growth and metastasis of lung cancer [26]. Moreover, Peixoto P et al found that inhibiting HDAC7 reduced the tumorigenic activity of human glioblastoma and provided a new opportunity for tumor treatment [27].…”
Section: Discussionmentioning
confidence: 99%